KINERJA KEUANGAN DAERAH KABUPATEN KONAWE KEPULAUAN - Kawatak, Salsabila Kamariah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research is entitled Konawe Islands Regency Regional Financial Performance. The aim is to find out the Regional Financial Performance of Konawe Islands Regency. The method of analysis is to use a comparative descriptive method that describes the financial performance of the Regional Government and uses financial ratios. The results showed that data processing and data analysis results that refer to the problems and research objectives, can be concluded as follows, The development of the effectiveness level of regional financial management in Kolaka Regency during the 2016-2020 fiscal year can be said to be very effective, namely by having an average effectiveness ratio above 100%. For further research, it is hoped that researchers can compare the financial performance of regencies or cities that have great potential in managing their regional finances, so that the research results have a clearer contribution that there are certain regencies or cities that have better financial performance than other regencies or cities.